Menentukan Strategi Sistem Informasi Bisnis - Maula, Muhammad Yaqi Dynal (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Business Information Systems (BIS) strategy is a crucial component in supporting the digital transformation process and achieving competitive advantage for an organization. However, various studies have shown that failure in information system implementation is often caused by a mismatch between business strategy and information technology strategy. This study aims to conceptually analyze the stages in formulating an effective BIS strategy through four main dimensions: internal and external situation analysis, strategic goal setting, appropriate technology selection, and evaluation and measurement of implementation results. This study uses a qualitative approach with a literature review method of the latest scientific sources relevant to strategic planning of information systems and digital transformation. The results of the study indicate that the success of a BIS strategy is determined not only by the level of technological sophistication, but also by strategic alignment, organizational readiness, IT governance, and ongoing evaluation mechanisms. With an integrative and business value-oriented approach, a BIS strategy can serve as a strategic tool in improving operational efficiency, decision-making quality, and organizational sustainability in the digital era.